Exploration of The Birth Planning and Complications Prevention Program Implementation - Pattipeilohy, Claudia Igreya; Maelissa, Merlin Margreth; Mainase, Josephina; Titaley, Christiana Rialine; Malakauseya, Maxwell Landri Vers; Nari, Janti Pare (Jurnal Kesehatan, 2023)
The Birth Planning and Complications Prevention Program or Program Perencanaan Persalinan dan Pencegahan Komplikasi (P4K) is an effort by the government to reduce the maternal mortality rate in Indonesia. This study aimed to determine the implementation of P4K to reduce maternal mortality in the catchment area of Waihaong Health Center Ambon in 2020. This was a qualitative study with a case study approach. Data collection was conducted in February-May 2020 in the catchment area of Waihaong Health Center. There were 13 informants interviewed in this study (nine pregnant women, two health workers, and two cadres). Data analysis was conducted using content analysis by identifying the emerging themes based on the research objectives. The results of this study show that the implementation of P4K has been running, but it has yet to be maximized because several P4K components still need to be completed. The pregnant woman prepares the components in the P4K sticker without any discussion with the midwife, and some pregnant women still choose to give birth with the help of a traditional birth attendant or â€œmama biangâ€. The mother's need for more knowledge about P4K and the lack of human resources as a program administrator was an obstacle to implementing this program. This study indicates that there is still a need for counseling for pregnant women to increase knowledge and awareness of the benefits of P4K and to carry out further training and collaboration between midwives and village cadres to improve P4K implementation.